Welfare Pluralism sebagai Metode Pemberdayaan di Dusun Gamol - Ulfiyatun Nadzifah (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2020)
This study attempts to examine the corporate social responsibility (CSR) program of PT. Pertamina (Persero) Fuel Terminal Rewulu which is based on a community empowerment program that has been running in several areas around the company, one of which is located in Dusun Gamol. This research uses a descriptive qualitative research approach. Data is collected through interviews, search for written documents, observations, and data analysis. This paper looks at the process and impact of empowerment that occurs in the region. I finds that empowerment here is an activity that aims to increase the ability in terms of processing the results of the etawa goat farm into milk powder products that are of sale value. With the help of the company it is hoped that the community can carry out more productive activities in managing goat's milk. The results showed that the empowerment in this hamlet went through several stages, as well as the program pioneered by corporate has a positive impact. The impact on mothers is mainly in increasing their skills and knowledge in goat milk production and being able to increase the income of group members.Studi ini berupaya mengkaji tentang program corporate social responsibility (CSR) PT. Pertamina (Persero) Fuel Terminal Rewulu yang berbasis program pemberdayaan masyarakat yang sudah berjalan di beberapa wilayah di sekitar perusahaan, salah satunya berada di Dusun Gamol. Penelitian ini menggunakan pendekatan penelitian deskriptif kualitatif. Data dikumpulkan melalui wawancara, penelurusan dokumen tertulis, observasi, dan analisis data. Tulisan ini melihat bagaimana proses dan hasil dari pemberdayaan yang terjadi di wilayah tersebut. Saya menemukan bahwa pemberdayaan disini merupakan kegiatan yang bertujuan untuk meningkatkan kemampuan dalam hal mengolah hasil dari peternakan kambing etawa menjadi produk susu bubuk yang bernilai jual. Dengan adanya bantuan dari pihak perusahaan diharapkan masyarakat dapat melaksanakan kegiatan yang lebih produktif dalam mengelola susu kambing. Hasil penelitian menunjukkan bahwa pemberdayaan di dusun ini melalui beberapa tahap, serta program yang dipelopori oleh perusahaan memiliki dampak positif. Dampak bagi ibu-ibu terutama dalam meningkatkan skill dan pengetahuan dalam produksi susu kambing serta mampu meningkatkan pendapatan anggota kelompok.